2020
DOI: 10.1021/acsmedchemlett.0c00521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14 Known Drugs as Inhibitors of the Main Protease of SARS-CoV-2

Abstract: A consensus virtual screening protocol has been applied to ca. 2000 approved drugs to seek inhibitors of the main protease (M pro ) of SARS-CoV-2, the virus responsible for COVID-19. 42 drugs emerged as top candidates, and after visual analyses of the predicted structures of their complexes with M pro , 17 were chosen for evaluation in a kinetic assay for M pro inhibition. Remarkably 14 of the compounds at 100-μM concentration were found to r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
195
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(202 citation statements)
references
References 34 publications
3
195
0
4
Order By: Relevance
“…This is returned to the preferability of these drugs to form a parallel hydrogen bond with HIS164 or HIS163, as in the case of chloroquine and triazavirin (Table 2 ). Several studies have indicated the vital role of the catalytic CYS145 residue in suppressing the protease activity [ 42 , 43 ]. As shown in Table 2 , seven out of the eighteen examined drugs exhibited a potential hydrogen bond with the catalytic CYS145 residue with bond lengths in the range of 2.06 − 2.99 Å.…”
Section: Resultsmentioning
confidence: 99%
“…This is returned to the preferability of these drugs to form a parallel hydrogen bond with HIS164 or HIS163, as in the case of chloroquine and triazavirin (Table 2 ). Several studies have indicated the vital role of the catalytic CYS145 residue in suppressing the protease activity [ 42 , 43 ]. As shown in Table 2 , seven out of the eighteen examined drugs exhibited a potential hydrogen bond with the catalytic CYS145 residue with bond lengths in the range of 2.06 − 2.99 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this this version posted December 2, 2020. ; https://doi.org/10.1101/2020.12.02.408112 doi: bioRxiv preprint binding of different HCV PI to SARS-CoV-2 M pro . [48][49][50][51][52][53][54][55][56][57][58][59][60][62][63][64][65][66][67][68]74 In several of these studies HCV PI were identified as top candidates following screening of large drug libraries, however, some of these studies also yielded contradictory results. Of these studies, 10 identified simeprevir 50,53,58,60,62,63,[65][66][67][68] , 5 paritaprevir 49,53,55,63,66 , 3 glecaprevir [54][55][56] , telaprevir 48,53,64 , boceprevir 48,57,59 and faldaprevir 48,60,…”
Section: Discussionmentioning
confidence: 99%
“…4860,6268,74 In several of these studies HCV PI were identified as top candidates following screening of large drug libraries, however, some of these studies also yielded contradictory results. Of these studies, 10 identified simeprevir 50,53,58,60,62,63,6568 , 5 paritaprevir 49,53,55,63,66 , 3 glecaprevir 5456 , telaprevir 48,53,64 , boceprevir 48,57,59 and faldaprevir 48,60,74 , 2 danoprevir 48,51 and asunaprevir 48,60 and 1 sovaprevir 48 , vaniprevir 48 , narlaparevir 48 and grazoprevir 52 to bind M pro . Recently, 4 groups reported studies of HCV PI voxilaprevir, boceprevir and simeprevir in cell-based antiviral assays.…”
Section: Discussionmentioning
confidence: 99%
“…Given the urgency of the current situation, several research groups are using in silico studies and in vitro assays to examine approved drugs as inhibitors of M3CLpro. For example, Ghahremanpour et al 27 tested a library of ca. 2000 drugs against M3CLpro.…”
Section: Introductionmentioning
confidence: 99%